Algecards : the mathematics clinic. (Singapore : The Mathematics Clinic, 2017)
AlgeCards comes in the teacher's pack and the student's pack. The teacher's pack is magnetic and is most suitable for use in classroom demonstration. The student's pack is a convenient manipulatives which students can use it through their years of education.
Didactisch materiaal.
Keywords: Educatieve spellen; Wiskunde -- Secundair onderwijs